ANALISIS PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI(Studi Kasus Pada Dinas Satuan Polisi Pamong Praja Kabupaten Mimika) - Elisabeth Letsoin; Nely Salu Padang (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The purpose of this study was to determine the effect of job satisfaction and work discipline on the performance of employees of the Civil Service Police Unit Office, Mimika Regency. The research method used is associative method with a quantitative approach. Data collection techniques were carried out by means of literature study, conducting observations, conducting interviews and distributing questionnaires. The analytical tool used in this study is path analysis. Path analysis is used to examine the influence or direct effect of job satisfaction and work discipline on employee performance at the Civil Service Police Unit Office, Mimika Regency. The results of the path test are job satisfaction 0.357 <0.05 and work discipline 0.000 <0.05. So the decision making is that job satisfaction and work discipline have a significant influence on employee performance at the Civil Service Police Unit Service, Mimika Regency